Republic of Estonia : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Estonia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation highlights that the economy of Estonia is now experiencing its most severe recession since the early 1990s. The financial sector has withstood the global financial turbulence well so far, but risks remain significant. Executive Directors have commended the Estonian authorities for the progress made in recent years in achieving economic convergence and deepening real and financial ties with the European Union. Directors have also commended the authorities for their planned substantial fiscal restraint in 2009.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet